ANALISIS PERSEPSI MASYARAKAT KOTA SIGLI TERHADAP PINJAMAN PEMBIAYAAN MIKRO OLEH BTPN SYARIAH DALAM PENINGKATAN USAHA UMKM DITINJAU DARI HUKUM ISLAM - Nansadiqa, Lisa (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2025)
BTPN Syariah Bank operates based on the principle of financial inclusion, providing financial products and services to the public and businesses. BTPN Syariah also provides a business capital financing loan program for MSMEs. This study uses a qualitative method with a descriptive analytical approach. Data collection methods were obtained through direct observation, interviews, and documentation. The subjects in this study were the MSME community in Sigli City, or customers, and BTPN Syariah. The results of the study concluded that the perception of the MSME community in Sigli City is more positive in understanding the differences between Islamic banks and conventional banks. MSME actors in Sigli City are greatly helped by the presence of BTPN Syariah Bank, which can improve the community's economy. Furthermore, the practice of debt receivables with both parties benefits each other, namely Muqtarid (borrower) receives a loan so that they can meet their needs. While Muqrid (the lender) also receives a profit. According to Islamic law, financing loans provided by BTPN Syariah for business development contain elements of usury, because the principle carried out between the borrower and BTPN Syariah bank uses the principle of interest and depends on the interest system applied in conventional banks. Therefore, any addition to the loan amount from the debtor is said to be usury, but it depends more on the background and the consequences that arise.